Inquiry-Based Linear Algebra Teaching and Learning in a Flipped Classroom Framework: A Case Study - Fredriksen, Helge; Rebenda, Josef; Rensaa, Ragnhild Johanne; Pettersen, Petter (Taylor & Francis, 2024)
Flipped Classroom (FC) approaches, which utilize video distribution via modern internet platforms, have recently gained interest as a pedagogical framework. Inquiry Based Mathematics Education (IBME) has proven to be a valid form of task design to motivate active learning and enhance classroom interactivity. This article presents a practical combination of introductory videos and inquiry-based class activities adoptable in a basic linear algebra course for stimulating students’ exploration of the underlying mathematics. Teachers’ and students’ work addressed in the article was realized in two case studies in engineering programs in Norway and the Czech Republic. The learning objective was to connect different interpretations of the matrix equation Ax=b, which is often perceived as challenging for engineering students. Feedback from classroom sessions, interviews, and questionnaires encourage further research and inspired us as teachers to closely examine the mathematics behind the task design.
Keywords: Inquiry-based mathematics education; flipped classroom; mathematics for engineering students